HIGH MORTALITY RATE AMONG OLDER POPULATION WITH COVID-19 IN ECUADOR. A RETROSPECTIVE CASE-STUDY (MARCH 15, 2020 – APRIL 15, 2020): Manuscrito recibido: 31/07/2020 Aceptado: 07/04/2021 - Mayorga Ramos, Arianna (2021)
Ecuador registered an increasing number of cases and deaths related to COVID-19 during an extended period. This case study aims to evaluate the epidemiological data reported by the Ministry of Public Health of Ecuador during a limited period (March 15- April 15). It focuses on differentiating the mortality rates among different age groups. Case- Fatality ratios were calculated with overall results of 4,94% mortality for COVID-19 positive patients of all ages by the end of the data collection period. It also indicated that patients aged ‘65 years or more’ had the highest Case-Fatality ratios (16,63%) followed by patients aged between ‘50-64 years old’ (7,37%). The lowest rate was 0% for patients aged 5-19 years. Therefore, indicating a high mortality rate among older patients. Case-Fatality ratios found in elderly Ecuadorian patients also appear to be slightly higher than estimated ratios from other countries. Presence of age-related comorbidities may be responsible on the increasing mortality among this age group. Social, economic, and cultural behaviors related to ethnicity (Latin-American) also may facilitate the spread of the virus among vulnerable groups, therefore, increasing mortality.